Reinforced Pores in Porous Steels Obtained with Matrix Soluble Space Holders. (2019) - Neves, G.O.; Paz, G.; Araya, N.; Binder, C.; Klein, A.N.
ABSTRACT: This paper presents a novel way to obtain reinforced pores by the dissociation of mixed carbides during sintering. Porous materials have a wide range of applications such as dampeners, light structures, etc. But usually pores act as points of stress concentration and crack nucleation, harming the mechanical properties of these materials. Methods have been developed to control the shape and size of pores but, until now, there are no techniques that allow reinforcing the material around the pores. To address this, steels were prepared by adding 1, 3 and 5 wt.% of Mo1.5 Cr0.5 C mixed carbide particles to a iron matrix by metal injection moulding. The results showed that during sintering, the dissociation of the carbide followed by the dissolution of the elements in the matrix generated rounded secondary pores with a reinforced vicinity, which increased the mechanical strength of the materials. The presence of rounded pores encircled by an enriched vicinity can allow the production of porous materials with exceptional fatigue strength and fracture toughness.